Hubungan Ketersediaan Jamban, Perilaku, dan Pengetahuan Masyarakat dengan Buang Air Besar di Kelurahan Legok Kota Jambi Tahun 2018 - Sondang Siahaan; Rina Fauziah (Poltekkes Kemenkes Yogyakarta, 2020)
To provide family latrines among general community is not easy, because it is closely associated with people participation in terms of their behavior, knowledge, and culture. The objective of this study is to understand the relationship between the availability of latrine, behaviors, and know-ledge of society with defecation behavior in Kelurahan Legok of Kecamatan Danau Sipin, Jambi. The study was a descriptive analytic with cross sectional approach. The size of study sample was 87 family heads. The study results show that 62 family heads already have latrine and the the rest 52 do not; 37 family heads have appropriate behavior, meanwhile the rest 50 have less appropriate behavior; 59 family heads have good knowledge, and as much as 28 family have less knowledge; 62 family heads defecating in latrine, meanwhile the other 25 defecate on river. Based on the study results, it can be concluded that there are significant relationship between the availability of latrine, attitudes, and knowledge of family heads with defecation behavior. For people of Kelurahan Legok, it is advised to organize latrine and septic tank “arisan” that is ad-dressed to those who do not have those facilities.